Pelatihan Teknologi Dan Aplikasi Cyber Prima Untuk Pemberdayaan Remaja Masjid Di Sangkapura - Muwafiqus Shobri (Jurnal Abdikarya Pembangunan, 2024)
Abstract: The community service project titled "Graphic Design Training, Video Editing, and Cyber PRIMA Application Socialization" at Istiqomah Patarselamat Mosque, Sangkapura, was initiated in response to the need of the Youth Mosque Committees across Sangkapura District to enhance their technological skills to better manage mosque activities. The issues faced included a lack of knowledge and skills in graphic design, video editing, and data management using technology applications. This project became increasingly urgent considering the growing importance of technology in supporting religious and social activities in the mosque. The project employed the Service Learning (SL) method, which combines academic learning with community service through intensive training and active participation. The results showed a 70% increase in participants' technological competencies based on pre-test and post-test comparisons, covering graphic design, video editing, and the use of the Cyber PRIMA application. Moreover, this project successfully transformed participants' attitudes, making them more positive and proactive in utilizing technology for mosque activities. For the program's sustainability, it is recommended that follow-up training and continuous support from relevant stakeholders be provided. Keywords: Graphic Design, Video Editing, Cyber PRIMA Application Abstrak: Pengabdian kepada masyarakat dengan tema "Pelatihan Desain Grafis, Editing Video, dan Sosialisasi Aplikasi Cyber PRIMA" di Masjid Istiqomah Patarselamat Sangkapura dilatarbelakangi oleh kebutuhan pengurus Remaja Masjid se Kecamatan Sangkapura untuk meningkatkan keterampilan teknologi guna mendukung pengelolaan kegiatan masjid. Masalah yang dihadapi adalah kurangnya pengetahuan dan keterampilan dalam desain grafis, editing video, dan manajemen data menggunakan aplikasi teknologi. Pengabdian ini menjadi sangat mendesak mengingat peran teknologi yang semakin penting dalam mendukung aktivitas keagamaan dan sosial di masjid. Pengabdian ini menggunakan metode Service Learning (SL), yang menggabungkan pembelajaran akademik dengan layanan masyarakat melalui pelatihan intensif dan partisipasi aktif. Hasilnya, terjadi peningkatan kompetensi teknologi peserta sebesar 70% berdasarkan perbandingan pre-test dan post-test, yang mencakup desain grafis, editing video, dan penggunaan aplikasi Cyber PRIMA. Selain itu, pengabdian ini berhasil mengubah sikap peserta menjadi lebih positif dan proaktif dalam memanfaatkan teknologi untuk kegiatan masjid. Untuk keberlanjutan program, disarankan adanya pelatihan lanjutan dan dukungan berkelanjutan dari pihak terkait. Kata kunci: Desain Grafis, Editing Video, Aplikasi Cyber PRIMA